Implication of microplastics on soil faunal communities — identifying gaps of knowledge. Issue 4 (1st December 2022) - Boots, Bas
Abstract : There is mounting evidence that plastic and microplastic contamination of soils can affect physico-chemical processes and soil fauna, as has been excellently summarised in many recently published meta-analyses and systematic reviews elsewhere. It has become clear that impacts are highly context dependent on, e.g. polymer type, shape, dose and the soil itself. Most published studies are based on experimental approaches using (semi-)controlled laboratory conditions. They typically focus on one or several representative animal species and their behaviour and/or physiological response — for example, earthworms, but rarely on whole communities of animals. Nevertheless, soil animals are rarely found in isolation and form part of intricate foodwebs. Soil faunal biodiversity is complex, and species diversity and interactions within the soil are very challenging to unravel, which may explain why there is still a dearth of information on this. Research needs to focus on soil animals from a holistic viewpoint, moving away from studies on animals in isolation and consider different trophic levels including their interactions. Furthermore, as evidence obtained from laboratory studies is complemented by relatively few studies done in field conditions, more research is needed to fully understand the mechanisms by which plastic pollution affects soil animals under realistic field conditions. However, field-based studies are typically more challenging logistically, requiring relatively large research teams, ideally of an interdisciplinary nature to maintain long-term field experiments. Lastly, with more alternative, (bio)degradable and/or compostable plastics being developed and used, their effects on soil animals will need to be further researched.